The prediction and verification of outcome of extracardiac conduits fontan based on computational fluid dynamics simulation - Zhang, Yong; Fang, Minhua; Wang, Zengwei; Liu, Yu; Zhang, Chunzhen; Wang, Zhenlong; Wang, Huishan (Frontiers in Physiology, 2022)
Objective: To predicte and verificate the outcome of Y-shaped extracardiac conduits Fontan for functional single ventricle based on preoperative computed tomography angiography (CTA) and computational fluid dynamics (CFD). Methods: Based on the preoperative CTA data of functional single ventricle (FSV), 4 types of spatial structures of extracardiac conduits were designed for 4 experimental groups: Group A, a traditional TCPC group (20 mm); Group B, a diameter-preserving Y-shaped TCPC (YCPC) group (branch 10mm); Group C, YCPC group (branch 12mm); and Group D, an area-preserving YCPC group (branch14mm). Four indicators including flow velocity, pressure gradient (PG), and inferior vena cava (IVC) blood flow distribution were compared. The optimal procedure was applied. The radionuclide lung perfusion, CTA, echocardiography, cardiovascular angiography and catheterization were performed postoperatively. Results: There were the lowest PG, the lowest flow velocity of branches, the highest energy efficiency, and a relatively balanced and stable distribution of IVC flow for group D. Subsequently, the group D, a handcrafted Y-shaped conduit (14mm) was used for the YCPC procedure. There was no postoperative PG between the conduit and pulmonary artery with normal pressure and resistance. IVC flow was distributed uniformly. Conclusion: CTA-based CFD provided more guidance for the clinical application of TCPC. A comprehensive surgical design could bring good postoperative outcome. Area-preserving YCPC has more advantages than TCPC and the diameter-preserving YCPC. The study effectively improved the feasibility of clinical applications of YCPC.